(untitled) (Journal of Medical & Health Sciences Review, 2025)
Blood transfusion is a cornerstone of modern medical care, critical for surgeries, trauma management, chronic illnesses, and maternal health. However, the safety of transfused blood relies heavily on effective screening protocols to prevent transfusion-transmissible infections (TTIs), including syphilis—a chronic, systemic, and often asymptomatic disease caused by Treponema pallidum. Given its potential to cause serious complications such as neurosyphilis, cardiovascular involvement, and congenital transmission, syphilis remains a significant global public health concern. This study was conducted to assess the prevalence of syphilis among healthy blood donors at Allied Hospital, Faisalabad, and to evaluate the effectiveness of current blood screening practices. Conducted from December 2023 to January 2024, the study included 16,206 blood donors, predominantly male (99.59%), mostly aged 18–30, and largely replacement donors from rural and suburban areas. Systematic sampling was employed, and blood samples were screened using immuno-chromatographic testing (ICT) and ELISA for confirmation. The seroprevalence of syphilis was found to be 0.9935%, a notable increase compared to earlier local findings. These results suggest a potential underestimation of syphilis burden in the community and indicate the need for routine donor screening, particularly in regions with limited healthcare access and awareness. The findings also reflect socio-economic challenges, insufficient sexual health education, and barriers to preventive care in underserved populations. Addressing these gaps through targeted public health campaigns, enhanced access to diagnostics, and continuous surveillance is essential to mitigate the transmission risk. This study contributes valuable epidemiological insight into syphilis prevalence in Pakistan and calls for stronger, equity-focused health strategies to ensure both the safety of blood transfusions and broader disease control efforts.